2) -3(4x+2)=-30
Open brackets: -12x-6=-30
-12x=-24
x=2
3) 35=(4-x)7
35=28-7x
7=-7x
x=-1
5) 4(3-2x)=52
12-8x=52
-8x=40
x=-5
6) -9 = -3(2x+1)
-9=-6x-3
-3=-6x
x=1/2
you do last 2 =P
2007-03-21 16:03:26
·
answer #1
·
answered by tennisboy152001 1
·
0⤊
0⤋
They all begin with "distribution", where the factor is applied to each term in the expression being multiplied.
For example, in 2, the left side is:
-3(4x +2) = -3*4x + -3*2 =
-12x -6
Having distributed your factor to the term being multiplied, you can replace the result in your equation
-3(4x +2) = -30
becomes
-12x -6 = -30
In an equality, you can multiply both sides by whatever you want, as long as BOTH SIDES are multiplied by the same thing. Let us multiply both sides by -1
-1(-12x -6) = -1(-30)
becomes
12x + 6 = 30
You can add or subtract the same value on BOTH SIDES. Let subtract 6 from each side:
12x + 6 - 6 = 30 -6
becomes:
12x = 24
You can divide both sides by whatever you want EXCEPT ZERO. Here, let us divide both sides by 12.
(12x)/12 = 24/12
x = 2
---
They are all pretty well on the same pattern. You can follow the same kind of procedure (of course, the numbers you use will change from one problem to the next).
---
There is no set order for the operations. You pick a strategy so that you end up with an x on one side and the answer on the other.
For example, begin number 6 by dividing both sides by -3 (remember that -3/-3 = 1 and that -9/-3 = +3)
(-9)/(-3)= -3(2x+1)/(-3)
becomes
+3 = 1(2x + 1) = 2x + 1
Let's subtract 1 (to leave only the term with x on the right side)
3 - 1 = 2x + 1 - 1
becomes:
2 = 2x
Let's divide by 2
2/2 = 2x/2
becomes
1 = x
2007-03-21 16:08:22
·
answer #2
·
answered by Raymond 7
·
0⤊
0⤋
2.) -3(4x +2)= -30
-12x -6=-30
-12x=-30+6
-12x=-24
x=-24/-12
x=2
3.)35=(4-x)7
35=28-7x
35-28=-7x
7=-7x
7/-7=x
-1=x
x=-1
5.) 4(3-2x)=52
12-8x=52
-8x=52-12
-8x=40
x=40/-8
x=-5
6) -9= -3(2x+1)
-9=-6x-3
-9+3=-6x
-6=-6x
-6/-6=x
1=x
x=1
7)5(3x+2)= -50
15x+10=-50
15x=-50-10
15x =-60
x=-60/15
x=-4
8) -36=(2-4x)6
-36=12-24x
-36-12=-24x
-48=-24x
-48/-24=x
2=x
x=2
to check just subtitute the value of x to the equation and see if they are equal
this the first and the answer you can get from me so try to study more and youll get the hang of it
2007-03-21 16:13:01
·
answer #3
·
answered by yugg 2
·
0⤊
0⤋
Solutions are below.
2) -3(4x + 2) = -30
4x + 2 = 10
4x = 10-2
4x = 8
x = 8/4
x = 2
------------
3) 35=(4-x)7
35/7 = 4-X
5 = 4-x
x = 4-5
x= -1
----------------
6) -9= -3(2x+1)
-9/-3 = (2x+1)
3 = 2X + 1
2 = 2X
1 = X
------------------------
7) 5(3X+2) = -50
3X + 2 = -50/5
3X + 2 = -10
3X = -10-2
3X = -12
X = -12 / 3
X = -4
--------------------------------
8) -36=(2-4x)6
-36/6 = (2-4X)
-6 = 2-4X
-6-2 = -4X
-8 = -4x
-8/-4 = x
2= x
==========================
2007-03-21 16:06:40
·
answer #4
·
answered by kums 1
·
0⤊
0⤋
I won't give you the answers but I will give you 2 good tips
1/ Algebra is a language to describe mathematical relationships between different changing things. So it must be learnt as a "language" just like you learn English. learning how to describe simple problems in this language is the key to master it.
2/ There is a lot of memory work involved into remembering the rules. But once you know some basic rules you can apply them to simplify the equations. There is also a bit of pattern matching when you swap things to make the equation looks simpler. For example: if you get one pair of equations like x + y = 10 and x = 5. You would need to match the x and 5 into the place of x in x + y = 10
I am teaching my child at 3rd grade to do this! By 8th grade you should have been doing quadratic equations and some fancy trigonometric maths. So you should work very hard to get the basics otherwise you will be a goner in maths.
2007-03-21 16:10:55
·
answer #5
·
answered by dmaivn 3
·
0⤊
0⤋
2) -12x-6=-30 so 12x+6=30 => 12x=24; x=2
3) 35 = 28-7x => x=-1
5) 12-8x=52 => -40=8x ; x= -5
6) -9 = -6x-3 =>-6=-6x ; x=1
7) 15x+10=-50 => 15x=-60 ; x=-4
8) -36=12-24x => -48=-24x ; x=2
2007-03-21 16:08:39
·
answer #6
·
answered by peateargryfin 5
·
0⤊
0⤋
Hi Rebeca,
All you need to do is solve for X. What you do to one side, you must do to the other- this is the basis of algebra.
For number 2, (line by line)
-3(4x+2)=-30
4x+2=10 (divide both sides by -3)
4x=8 (subtract 2 from both sides)
x=2 (divide both sides by 4)
Number 3 (line by line)
35=(4-x)7
4-x=5 (divide both sides by 7)
-x=1 (subtract 4 from both sides)
x=-1 (multiply both sides by -1)
Number 5 (line by line)
4(3-2x)=52
3-2x=13 (divide both sides by 4)
-2x=10 (subtract 3 from both sides)
x=-5 (divide both sides by -2)
Number 6 (line by line)
-9=-3(2x+1)
2x+1=3 (divide both sides by -3)
2x=2 (subtract 1 from both sides)
x=1 (divide both sides by 2)
Repeat this process for 7 and 8. Solve for X and remember, what you do to one side, you must do to the other. Good Luck!
2007-03-21 16:07:36
·
answer #7
·
answered by Kyle M 1
·
0⤊
0⤋
6)
-9=-6x-3
-9+3=-6x
-6=-6x
x=1
7)
15x+10=-50
15x=-50-10
15x=-60
x=-60/15
x=-4
8)
-36=12-24x
-36-12=-24x
-48=-24x
x=2
If you don't understand the steps ask someone to explain them to you, maybe your teacher. Otherwise you'll have problems. good luck!
2007-03-21 16:25:50
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
The first thing you need to do is distribute. Then from there is becomes a very easy problem. Add, subtract multiply or divide in order to get x by itself.
2007-03-21 16:05:59
·
answer #9
·
answered by lxlalwaysdreaminlxl 1
·
0⤊
0⤋
8y-7x+2y-x make everything addition so that you can use the commutative property 8y+-7x+2y+-x like terms are the terms that have the same variable so combine them 10y+-8x you treat the negative x like -1x so you know the value of the coefficient
2016-03-28 23:06:43
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋